Characterization of a new Autographa californica multiple nucleopolyhedrovirus (AcMNPV) polyhedra mutant - Ribeiro, Bergmann Morais (2009)
In the very late phase of baculovirus infection, virions are occluded in a crystalline matrix called polyhedra, which is mainly composed of polyhedrin. This protein is highly conserved among baculoviruses and changes in its amino acid sequence may lead to mutant polyhedra. During the purification of an AcMNPV recombinant virus, a mutant virus was isolated. Structural and ultrastrutural analysis by light and transmission electron microscopy (TEM) of insect cells infected with this mutant virus did not show polyhedra formation and differed from the wild-type infection by the presence of a proteinaceous mass dispersed in the cytoplasm and nucleus of the infected cells, which was confirmed by immunogold labelling to be polyhedrin. The polyhedrin gene was amplified by PCR and sequenced. The only change observed was the substitution of a G to a T at the nucleotide +352, which resulted in a Val to Phe change. A recombinant virus was constructed by transferring the mutant gene into a polyhedrin negative virus. The phenotype of this recombinant virus was the same as the mutant one, confirming that this single mutation alone was responsible for the mutant phenotype.